Análisis de mecanismos alternativos de ejecución de proyectos de inversión pública con participación del sector privado en la región Loreto periodo 2018-2023 - Mori Alvan, Mayra Iris (2025)
The study analyzed alternative mechanisms to execute public investment projects with private participation in Loreto, 2018-2023, covering 9 Public Works and 2 Public Private Association projects, using documentary analysis to obtain official information. The variable alternative project execution mechanisms are based on an instrument called a data collection matrix, created for research. The design was experimental, comparative, transactional, basic research, quantitative and descriptive. The planned investment in Works by Impuesto is S/ 90,768,157 with a financial execution of 51%, covering 9 projects; the investment in the Public-Private Association mechanism is estimated at S/ 1,881,920.61, with an execution of 43% in 2 projects, in the Loreto region, between 2018 and 2023. In summary, the investment in alternative methods of executing projects of public investment with the private sector is smaller than the average investment of the invierte system.